Women´s swimming - selected methods for optimising competitive training - Nadobnik, J.; Wiazewicz, A. (Acta Kinesiologica, 2022)
This article presents selected results of the authors' research into the topic of strength ability of female competitive swimmers with the aim of optimising training to achieve the best possible results. Apart from a review of the literature on sports swimming, muscle strength analysis and the specificity of strength training in sports swimming, characteristic movements of the upper limbs observed during sports swimming are discussed and the results of previous research concerning the measurement of strength in female competitive swimmers are presented. The study group consisted of 12 female swimmers. Measurements were carried out twice. The first measurement took place in January 2014. After completing this series of measurements, the necessary changes were proposed. Measurement two took place in January 2015. Additionally, they had to be at least 14 years old. The subjects were included in the dietary catering. A high-protein and high-carbohydrate diet was used, tailored to the needs of each female athlete. The daily routine and lifestyle of the subjects consisted of two workouts (morning and afternoon). The lifestyle of the subjects and their nutrition can be considered comparable. To this end, laboratory measurements of biomechanical muscle properties were used, and land tests (static and dynamic), tethered swimming tests and isokinetic tests using state-of-the-art dynamometers were also conducted. The isokinetic arm measurement method should be used for the ongoing and periodic monitoring of female high level competitive swimmers. A specific annual strength training intervention is not sufficient to induce positive changes in arm muscle strength parameters in female competitive swimmers. General development, targeted and specific strength training of the arm muscles as well as compensatory and compensatory programmes tailored to the individual needs of high level competitive swimmers should be planned and applied to consistently eliminate possible deficiencies in strength parameters. Changes in some strength parameters of arm muscles over a yearly cycle had a positive effect on sports performance. Long-term, individualised programmes of improvement of specific strength parameters of arm muscles should be conducted to improve the performance of high-level sports swimmers.